2005
DOI: 10.4049/jimmunol.174.3.1602
|View full text |Cite
|
Sign up to set email alerts
|

Immune Activation of Type I IFNs by Listeria monocytogenes Occurs Independently of TLR4, TLR2, and Receptor Interacting Protein 2 but Involves TANK-Binding Kinase 1

Abstract: Type I IFNs are well established antiviral cytokines that have also been shown to be induced by bacteria. However, the signaling mechanisms regulating the activation of these cytokines during bacterial infections remain poorly defined. We show that although Gram-negative bacteria can activate the type I IFN pathway through TLR4, the intracellular Gram-positive bacterium Listeria monocytogenes (LM) can do so independently of TLR4 and TLR2. Furthermore, experiments using genetic mutants and chemical inhibitors s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 35 publications
(48 reference statements)
7
81
1
Order By: Relevance
“…The results presented here argue that Nod proteins do not significantly influence the activation of the type I IFN pathway mediated by this unidentified bacterial DNA sensor. This is in agreement with a previous study which demonstrated that intracellular detection of invasive bacteria results in the activation of the type I IFN responses, independently of receptor-interacting protein 2, a critical adaptor protein acting downstream of Nod1 and Nod2 [27].…”
Section: Discussionsupporting
confidence: 94%
“…The results presented here argue that Nod proteins do not significantly influence the activation of the type I IFN pathway mediated by this unidentified bacterial DNA sensor. This is in agreement with a previous study which demonstrated that intracellular detection of invasive bacteria results in the activation of the type I IFN responses, independently of receptor-interacting protein 2, a critical adaptor protein acting downstream of Nod1 and Nod2 [27].…”
Section: Discussionsupporting
confidence: 94%
“…As shown in Fig. 6A, LM infection resulted in increased serum levels of IFN-␤ that peaked at 48 h after infection and were similar in WT and MyD88 Ϫ/Ϫ mice, confirming previous reports that IFN-␤ production by LM is MyD88 independent (25). IFN-␤ serum levels were not increased in LM-infected IFN␣R1 Ϫ/Ϫ mice (Fig.…”
Section: Prevention Of Tolerance By Lm Infection Is Mediated By Type supporting
confidence: 76%
“…The invasion of the cytosol triggers early inflammatory responses and, ultimately, protective immunity that depends both on innate and adaptive immune responses. Innate immune events include the production of MCP-1 (CCL2) and type I IFNs in a MyD88-independent but NF-B-dependent, manner (25). The secretion of MCP-1 by LM-infected cells results in the emigration of neutrophils and blood CD11b ϩ monocytes out of the bone marrow (26).…”
Section: Linical Data Support a Correlation Between Viral Infectionsmentioning
confidence: 99%
“…This unique property of LLO may be essential for the intracellular parasitism of L. monocytogenes. Activation of LLO by acidification of phagosomes containing L. monocytogenes is an important step in bacterial escape because the inhibition of phagosomal acidification by H + -ATPase inhibitors, bafilomycin A 1 or concanamycin A, results in the prevention of bacterial escape into the cytoplasm (Beauregard et al, 1997;O'Connell et al, 2005). Also, functional inactivation at a neutral pH is likely essential for intracellular parasitism of this bacterium.…”
Section: Introductionmentioning
confidence: 99%